TEOLOGI HAKIMIYAH: BENIH RADIKALISME ISLAM - Iman Fauzi Ghifarie (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
This article examines the theological issues called hakimiyah as the seeds of extremism, fundamentalism, radicalism religion (Islam) that manifests itself in the behavior and acts of violence in the name of religion. The rise of radicalism among young people in the form of violence, terrorism, suicide bombing is coming from theology hakimiyah and Istisyhad doctrine (martyrdom) in order to get guarantee into heaven surrounded by 40 angels. It is because, they always spread hatred and hostility and beliefe to takfiri concept (infidelity) to resolve any different opinion,a belief that led to vigilante, even to take the life of another person as the main ticket to heaven. If the actions and behaviors that hurt the conscience and the humanitarian aspect continues to be done systematically, and sustained by the younger generation, then what would the fate of Mother Earth become? Of course, it is possible to give the birth of the Islamic State of Indonesia Malayasia. Meanwhile, Islam forbids any acts that damage, destroy, injure, and kill for no good reason. Even in a war, moral principles, morality, and ethics should be a guide and reference. Radicalism, terrorism, limbs and destruction have no religion nor country. Everyone who embrace the ideology which spread terror to the people who live safely, and bring damage to plants and animals are terrorist. No one can give any sentence of punishment